(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The study aims to analyze and diagnose the reality of marketing intelligence in Iraqi banks with its four dimensions (customer understanding, market understanding, product intelligence, competitors intelligence). The study was conducted on a number of banks in the province of Kirkuk, namely (Al-Noor Bank, One June Bank, Al-Rashid Bank). The size of the final sample population was (57). The researcher relied on the statistical analysis of the data collected from the banks surveyed. I rely on the five-point Likert scale through the questionnaire, which was designed as a means of data collection. A number of conclusions and recommendations were reached, including that the banks under study should give a more important character to marketing intelligence.